Preterm cerebral microcirculation assessed with color Doppler: A pilot study - Raets, M.M.A.; Govaert, P.; Goos, T.G.; Reiss, I.K.M.; Jonge, R.C.J. de; Dudink, J. (Journal of Pediatric Neuroradiology, 2014)
AIM: Pilot study to explore feasibility of a color Doppler technique for monitoring cerebral perfusion at the level of microvessels.METHODS: Between March 1st, 2011, and January 30th, 2013, all admitted infants born before 29 weeks of gestation were eligible for Doppler imaging. Perfusion images were acquired in a standard coronal plane. Image quality was assessed by two authors (MR, PG). The region of interest (ROI) was manually selected. A segmentation tool was developed to separate color data from the greyscale 2D images, leading to a percentage and number of color pixels in the image (Doppler color index; DCI). Intra- and inter-observer agreement was analyzed.RESULTS: Intra- and inter-observer agreement for placement of ROIs was good (bias −0.24 resp. −0.74 percentage points). Color Doppler was able to depict microvessels in cortex, white matter and deep grey matter. The median DCI in a region of cortex-white matter was 7.8% with a wide range (1.4%–25.6%). There was no significant difference between the left and right hemisphere (Mann-Whitney U, P-value 0.61). Clinically relevant observations were tabulated, e.g. distant effect of germinal matrix hemorrhage (GMH) on regional perfusion.CONCLUSION: Sonographic small vessel visualisation may help understand pathogenetic mechanisms related to perfusion and is valuable to monitor effects of treatment.
Keywords: Preterm infant; microcirculation; cerebral; color Doppler imaging